Determinan karakteristik keuangan perusahaan terhadap manajemen pajak - Agoestina Mappadang; Wahyudin Wahyudin; Jusuf Luther Mappadang; Agustinus Miranda Wijaya (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2022)
This study aims to determine the factors that influence tax management by using the effective tax rate as a measuring indicator. Several factors of the company's financial characteristics are used, such as capital intensity ratio, profitability, leverage, and size. This study analyzes the effect of capital intensity ratio, profitability, leverage, and size on tax management in manufacturing companies listed on the Indonesia Stock Exchange. The use method is quantitative. The sample was selected through purposive sampling; as many as 244 data were used for five years from 2017 to 2020. The data collection method is the non-participant observation method. Data acquisition sources using secondary data and data processing techniques use multiple regression tests. This study result concludes that it has a significant positive effect on the company's profitability variable on tax management and a positive relationship between the capital intensity ratio variable on tax management. Furthermore, a positive impact of company size on tax management has been confirmed. At the same time, leverage is also significantly positive on tax management.